Determinan Penyebab Perilaku Sedentary Lifestyle Pada Remaja : Studi Pada Siswa SMAN 8 Luwu Utara Dan SMAN 19 Luwu Utara - Alifiah Syahra Gading; Andi Asrina; Harpiana Rahman (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2026)
Sedentary behavior is a risk factor for various health problems in adolescents, characterized by low physical activity and high time spent sitting or lying down. Various individual, family, and environmental factors are suspected to contribute to the development of sedentary behavior in adolescents. This study aimed to determine the factors associated with sedentary behavior in adolescents at SMAN 8 and SMAN 19 in North Luwu. This study used a quantitative, cross-sectional design. The study population consisted of all 605 students at SMAN 8 in North Luwu and 100 students at SMAN 19 in North Luwu. The study sample comprised 196 eleventh-grade students from both schools. Data were collected using a questionnaire and analyzed univariately and bivariately with a 95% confidence level (α = 0.05). The results showed that at SMAN 8, North Luwu, there was a significant relationship between parenting style (p = 0.005), knowledge (p = 0.049), attitude (p = 0.011), technology exposure (p = 0.006), and economic status (p = 0.001) and sedentary behavior. Similar results were also found at SMAN 19, North Luwu, where parenting style (p = 0.035), knowledge (p = 0.032), attitude (p = 0.017), technology exposure (p = 0.018), and economic status (p = 0.015) were significantly associated with sedentary behavior. This study concluded that parenting style, knowledge, attitude, technology exposure, and economic status are associated with sedentary behavior among adolescents in both urban and rural areas. Therefore, efforts are needed to increase physical activity through health education, monitoring technology use, and family support to foster an active and healthy lifestyle among adolescents.